The "good fatty" is a dancing fatty: Fat archetypes in reality television. Issue 3 (2nd September 2019) - Cameron, Layla
ABSTRACT: While fatphobia runs rampant in traditional reality television programs, the advancement of the body-positive movement has made media representations of fat people far more complex. Utilizing TLC's My Big Fat Fabulous Life as a case study, the author addresses how the introduction of body positivity into the reality television industry has offered freedom from fat shame only to those who fit into a "good fatty" archetype.